UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KULIT BATANG SANTIGI (Pemphis acidula) TERHADAP BAKTERI Escherichia coli DENGAN METODE DIFUSI CAKRAM - Pia Batmomolin; Cut Bidara Panita Umar; Arga Rizqiati Wahid (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
Santigi plant (Pemphis acidula) is a plant from the Lythraceae family in the form of a dense shrub or small tree. People in Buru Regency use this plant as a daily treatment, one of which is to treat diarrhea. Santigi plant (Pemphis acidula) contains chemical compounds that function as antibacterial. Antibacteria are substances that inhibit and kill. Escherichia coli is a gram-negative bacterium that causes infection in the intestines and causes diarrhea. This study aims to determine the antibacterial activity of the bark of santigi (Pemphis acidula) against bacteria Escherichia coli. This research is an experimental laboratory research. The study used a thick 95% ethanolic extract of santigi stem bark (Pemphis acidula), variations in extract concentration were 20%, 40%, 60%, 80%, and 100%, for negative control using distilled water and for positive control using cotrimoxazole. In antibacterial testing of the ethanolic extract of the santigi stem bark (Pemphis acidula) against Escherichia coli bacteria, it showed that at concentrations of 20%, 40%, 60%, 80% and 100% sensitive to inhibit bacterial growth with an inhibition zone diameter of 12.3 mm, 14.17 mm, 16.00 mm, 17.00 mm, and 17.67 mm. The negative control did not have antibacterial activity and did not have an inhibition zone diameter, positive control had an inhibition zone diameter of 39.33 mm. The results showed that the bark of santigi has an inhibitory power against the growth of Escherichia coli bacteria with a strong category.